TEACHING READING COMPREHENSION BY APPLYING CLOZE PROCEDURETECHNIQUE - Suryani (English Education Department, 2014)
This research is intended to investigate the effect of cloze procedure technique application in teaching reading comprehension to the eleventh grade students of Senior High School (SMA) Negeri 8 Banda Aceh. The main purpose was to know whether the students who were taught by using cloze procedure technique would get a better performance in their reading comprehension compared to those who were not. The reading material given to the students was narrative text. The population and sample of the study was the eleventh year students of Senior High School Number 8 (SMA Negeri 8) Banda Aceh which consists of 58 students; 29 in each class. The data of this research was collected by giving the pre-test and post-test in every meeting which includes four meetings. The test given was in form of cloze procedure especially fixed-deletion technique. The data was analyzed using SPSS 15,0. The result of the data analysis can be seen from the result of the post-test of the experimental group in which that the mean of the post-test of the experimental group in the first meeting was 52,28, in the second meeting was 48,97, in the third meeting was 60,00, and in the fourth meeting was 76,38. Moreover, the mean score of the post-test of the control group was 44,14 in the first meeting, 42,59 in the second meeting, 44,83 in the third meeting, and 54,83 in the fourth meeting. By comparing t-test score of the experimental group and t-table score, it shows that the result of t-test in the first meeting is -5,508 while the result of t-table at a level of significance with a = 0,05 is 2,048. The t-test score in the second meeting is -4,930, in the third meeting is -9,452, and the fourth meeting is -21,216. From all t-test score, it indicates that the t-test score < the t-table 2,048. It means that the alternative hypothesis is accepted. So, it can be concluded that the students who were taught by using cloze procedure technique have a better performance than those who were not. As the follow up for this research, it is suggested that English teachers should use various technique in teaching. In teaching reading comprehension, cloze procedure technique can be an alternative to be applied in teaching English.